QT interval dynamics and triggers for QT prolongation immediately following cardiac arrest. (May 2021) - Cohen, Roi Bar; Dai, Matthew; Aizer, Anthony; Barbhaiya, Chirag; Peterson, Connor; Bernstein, Scott; Park, David S.; Spinelli, Michael; Chinitz, Larry A.; Jankelson, Lior
Abstract: Background: The prolongation in QT interval typically observed following cardiac arrest is considered to be multifactorial and induced by external triggers such as hypothermia therapy and exposure to antiarrhythmic medications. Objective: To evaluate the corrected QT interval (QTc) dynamics in the first 10 days following cardiac arrest with respect to the etiology of arrest, hypothermia and QT prolonging medications. Methods: We enrolled 104 adult survivors of cardiac arrest, where daily ECG was available for at least 3 days. We followed their QT and QRS intervals for the first 10 days of hospitalization. We used both Bazett and Fridericia formulas to correct for heart rate. For patients with QRS < 120 we analyzed the QTc interval (n = 90) and for patients with QRS > 120 ms we analyzed the JTc (n = 104) vs. including only the narrow QRS samples (n = 89). We stratified patients by 3 groups: (1) presence of ischemic heart disease (IHD) (2) treatment with hypothermia protocol, and (3) treatment with QTc prolonging medications. Additionally, genetic information obtained during hospitalization was analyzed. Results: QTc and JTc intervals were significantly prolonged in the first 6 days. Maximal QTc/JTc prolongation was observed in day 2 (QTcB = 497 ± 55). There were no differences in daily QTc/JTc and QRS intervals in the first 2 days post arrest between patients with or without hypothermia induction but such difference was found with QT prolonging medications. All subgroups demonstrated significantly prolonged QTc/JTc interval regardless of the presence of IHD, hypothermia protocol or QTc prolonging medication exposure. Our results were consistent for both Bazetts' and Frediricia correction and for any QRS duration. Prolongation of the JTcB beyond 382 ms after day 3 predicted sustained QTc/JTc prolongation beyond day 6 with an ROC of 0.78. Conclusions: QTc/JTc interval is significantly and independently prolonged post SCA, regardless of known QT prolonging triggers. Normalization of the QTc post cardiac arrest should be expected only after day 6 of hospitalization. Assessment of the QTc for adjudication of the etiology of arrest or for monitoring the effect of QT prolonging medications may be unreliable.